Social, Systemic, Individual-Medical or Cultural? Questionnaire on the Concepts of Disability Among Teacher Education Students - Gebhardt, Markus; Schurig, Michael; Suggate, Sebastian; Scheer, David; Capovilla, Dino (Frontiers in Education, 2022)
The individual-medical concept of disability, whereby disability is believed to be caused by some intractable impairment, is perhaps the most widely held view in society. However, other concepts exist with which teachers in inclusive schools should be familiar (e.g., social, systemic), to better inform teacher behavior, attitudes and understanding. We therefore developed an instrument to capture education students’ concepts of disability. We constructed the questionnaire according to four theoretical models of disability (individual-medical, social, systemic, and cultural concepts), which are commonly used in inclusive teacher education, and validated this on a sample of 775 education students. Additionally, we administered the Attitudes towards Inclusion Scale (AIS) and measured key demographic variables. The instruments, data and analysis code used are available online at https://osf.io/dm4cs/. After dropping redundant items, a shortened form of the questionnaire contained 16 items, with satisfactory psychometric values for scales pertaining to four concepts of disability (CFI = 0.963, TLI = 0.955, RMSEA = 0.037, SRMR = 0.039). These four concepts of disability showed small correlations with the AIS, indicating that our questionnaire measured an independent construct. The more experience education students had with disability and the more courses they had attended on inclusive education, the more likely they were to agree with the social concept of disability. The questionnaire shows promise in measuring concepts of disability and might be used to stimulate students’ critical reflection during teacher education.